A Medium Guardian for Enhanced Dependability in Safety-Critical Wireless Systems - Almeida, João Miguel Pereira de (2020)
According to the recent perspectives for the next generation of mobile networks (5G), future wireless communications will be able to support the operation of safety-critical systems, such as remote surgery or vehicle platooning. For that purpose, high reliability and availability values (> 99.999%), as well as low end-to-end delay (<; 1 ms), are included in the requirements specification. In order to achieve these goals, novel solutions will need to be introduced both at the communications devices and at the network protocols. Fault tolerance mechanisms are good candidates to attain such dependability attributes. In this paper, a medium guardian concept is proposed to guarantee fail-silent behavior, both in time and value domains, for the nodes of a wireless network. After a generic description of the wireless medium guardian concept, its application to the case of ETSI ITS-G5-based vehicular communications is demonstrated. In this way, the design and practical implementation of a medium guardian for real-time vehicular communications is reported, together with the experimental evaluation of this first prototype. The obtained results demonstrate the low latency of the fault detection mechanism and the effectiveness of the guardian in preventing error propagation to other nodes of the network.